Global China at 20: Why, How and So What?. (June 2022) - Lee, Ching Kwan
Abstract : The recent two-decade-long march of "global China" – manifested as outward flows of investment, loans, infrastructure, migrants, media, cultural programmes and international and civil society engagement – has left sweeping but variegated footprints in many parts of the world. From "going out, " officially announced in the year 2000, to the Belt and Road Initiative (BRI) and Made in China 2025, and from the developing world to advanced industrialized democracies, state-endorsed campaigns are but tips of a much more momentous iceberg. Numerous Chinese citizens and private corporations have also participated in a global search for employment, business, investment and educational and emigration opportunities. International reactions to the increasingly ubiquitous presence of China and the Chinese people in almost every corner of the world have evolved from a mixture of anxiety and hope to a more explicitly critical backlash. Terms such as "sharp power, " "debt-trap diplomacy" and the "new Cold War" bespeak the West's dominant perception today of China as a threat to be contained.